Involving Indigenous Community in Tourism Activities: Strategies and Interventions. - Delphine Kessy (African Journal of Hospitality, Tourism and Leisure, 2017)
The study revolves around involving indigenous communities in tourism activities. It addresses strategies and interventions for involving the indigenous communities in tourism. From a development perspective, tourism ventures are considered successful if indigenous communities are involved and or have some control over them. Tourism ventures such as Domestic Owned Tourism Enterprises (DOTEs), Cultural Tourism Enterprises (CTEs) and Destination Management Organizations (DMOs) were studied to seek to understand the interventions for involving indigenous communities in tourism from three different perspectives. These were policy, institution and supply side/ enterprise perspectives. The study was guided by the three research questions: What are the opportunities for indigenous people participation in tourism? What are the interventions for involving indigenous people in the business of tourism? and how is the business of tourism organized to ensure the indigenous benefit from tourism? The article advocates that involvement of indigenous communities in tourism is a result of different strategies and interventions that aim to empower them to gain control over the industry as they benefit from it.